Tarascan Copper Metallurgy - Maldonado, Blanca Estela (Archaeopress Pre-Columbian Archaeology Ser., 2019)
A study which provides valuable insights into the nature of metal production and the development of technology and political economy in ancient Mesoamerica, offering a contribution to general anthropological theories of the emergence of social complexity.